Design of Defective EBG Structures for Dual-Band Circular Patch MIMO Antenna Applications - Xiaoyan Zhang; Yuting Chen; Haitao Ma; Liwei Li; Huihui Xu, (Applied Computational Electromagnetics Society Journal (ACES), 2019)
Usually, a reasonably designed electromagnetic band-gap (EBG) structure can reduce the surface wave of an antenna. However, it may take a long time to design. In this paper, a dual-band circular patch multiple-input multiple-output (MIMO) antenna on an EBG surface is proposed. Defects are simply introduced into rows and columns of the EBG cells. In this way, the band-gap bandwidth (BG-BW) of those cells can be as large as 29.2%, which enables the EBGs can cover two frequency bands with a large interval, and to generate over 25 dB isolation between the antenna elements, as well. The measured results show that the proposed antenna, incorporating defective EBGs, operates at 5.71-5.97 GHz and 6.31-6.54 GHz. The -10 dB impedance bandwidth of the antenna is extended by 28.9% and 27.8% at the low and high frequency band. In addition, its gain is enhanced by 5 dB and 6.9 dB, and its back radiation decreased by 15 dB and 10.3 dB at the resonant frequencies of 5.75 GHz and 6.44 GHz, respectively. The proposed design may have many applications in communication systems.